Discovery of characteristic chemical markers for inspecting sulfur-fumigated Radix Angelicae Sinensis by ultra-high performance liquid chromatography–quadrupole/time-of-flight mass spectrometry based metabolomics and chemical profiling approach. (October 2015) - Bai, Ying-Jia; Xu, Jin-Di; Kong, Ming; Gao, Qiong; Liu, Li-Fang; Li, Song-Lin
Abstract: An UHPLC–QTOF-MS/MS based metabolomics and chemical profiling approach was developed to identify the characteristic chemical markers for inspecting sulfur-fumigated Radix Angelicae Sinensis (S-RAS). Two sulfur-containing compounds in S-RAS were discovered and deduced to be (3 Z )-6-sulfite-ligustilide and (3 E )-6-sulfite-ligustilide. Furthermore, utilizing extraction ion method with the typical ion ( m/z 271.06) of (3 Z )-6-sulfite-ligustilide/(3 E )-6-sulfite-ligustilide as the diagnostic ion, another six sulfur-containing components were determined in S-RAS, and identified as 6, 8-disulfite-ligustilide and 8-sulfite-ligustilide or their isomers. The generation mechanisms of these compounds were proposed as the addition reaction of sulfurous acid with ( Z )-ligustilide and/or ( E )-ligustilide, two major naturally occurring components in RAS, at the double bonds of C6C7 and C3C8 positions. Using (3 Z )-6-sulfite-ligustilide and (3 E )-6-sulfite-ligustilide as the chemical markers, fourteen of sixteen batches of commercial RAS samples were inspected to be S-RAS, suggesting that the newly generated sulfur-containing compounds could be used as characteristic chemical markers for inspecting S-RAS among commercial RAS samples. Highlights: A metabolomics approach was developed to find characteristic chemical markers of S-RAS. Eight novel sulfur-containing ligustilide derivatives were identified as characteristic chemical markers of S-RAS. The possible mechanisms involved in generation of sulfur-containing chemical markers were deduced. The chemical markers with diagnostic ion at m/z 271.06 were selected to inspect S-RAS.